GENDER EQUITY AND INCLUSION OF TRANSGENDER STUDENTS IN INDIAN HIGHER EDUCATION: AN ANALYSIS OF THE NEW EDUCATION POLICY 2020 - Mittal, Sangeeta; Goel, Ina (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the status of transgender students within Indian higher education institutions, focusing on the systemic, societal, and policy-level barriers that affect their access, participation, and well-being. Despite the legal recognition of transgender individuals by the Supreme Court of India in the NALSA judgment (2014), the implementation of inclusive educational practices remains inconsistent and insufficient. Through a multidisciplinary lens, the paper examines institutional practices, curriculum sensitivity, faculty and peer attitudes, and infrastructural support—or the lack thereof—that impact transgender students' academic and personal development. The study advocates for the transformation of higher education into a more equitable and inclusive space through policy reforms, awareness programs, and structural changes aimed at affirming transgender identities and rights. The research underscores the urgency for educational institutions to move beyond tokenism and actively engage in creating safe, supportive, and affirming environments for all students, regardless of gender identity.